A Singaporeanised war : the localisation of WWII in Singapore's school history curriculum - Tan, Zachary Zhi-Yu (Nanyang Technological University, 2022)
The topic of World War Two (WWII) in Singapore is regarded as a significant chapter in the history of the nation-state and occupies an indispensable aspect of the Singaporean national identity and the state’s nation-building discourses. Yet, despite its critical role in the construction of the Singaporean nation-state, representations of WWII in Singapore’s history education had been far from an unchanging fixture in Singapore’s history syllabuses and textbooks. This project aims to investigate how WWII had been ‘localised’ in Singapore’s history curriculum at different points in Singapore’s post-independence period, allowing the event to become a conflict that the nation-state could claim as its own. It reveals how the process of localisation that representations of WWII exhibited in history textbooks at different points in Singapore’s history directly correlated with how the state approached the function of history education at the time. In addition, the process of localising WWII served to ‘decolonise’ what was, in essence, a colonial conflict and an event regarded by the state as part of colonial history within Singapore’s history curriculum to reframe it as a more viable post-colonial nation-building resource.